PARADIGMA MAQASHID AL-SYARI’AH DALAM MENJAWAB DINAMIKA EKONOMI KONTEMPORER - Dahlan, Moh (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2019)
In the contemporary era that is completely digital, the behavior or culture of Indonesian people has shifted to meet their needs. The shift in behavior or culture is sometimes not only in the form of sustainable innovation but also in the form of disruptive innovation, so as it requires an effort of ijtihad (independent reasoning) to address it. This type of research is a normative study using a library research approach. The results show that the application of contemporary digital economic systems becomes primary needs (dlaruriyat), at least secondary needs (hajiyyat), so that Indonesian (Muslim) people are most likely required to do so, not only in the form of sustainable innovations but also disruptive innovations applied in digital economic systems in guaranteeing the safety of public rights (hifdz al-mujtama') and building economic progress as the application of the principle of hifdz al-mal (preservation of wealth).